Internal environment analysis of Quezon City Public Library and its branch libraries - Castro, Janice C. (2008)
This is a preliminary study about the possibility of establishing a computer-network among the Quezon City Public Libraries. The researcher looked into the current condition of the Quezon City Main Library and eight of its branch libraries namely: Pasong Tamo, Pansol, Novaliches, Marilag, Escopa, Project 7, Project 8 and Cubao Public Libraries. The researcher assessed these libraries as to their: management, collection and services, staff and organization, technology and facilities and budget. The researcher used 31-item survey questionnaire to gather the necessary information. This was answered by the Librarian-in-Charge of each branch library. Added to that, the researcher also consulted the statistical records of each branch library. It included: the number of their users (grouped according to type), the number of collection used and borrowed (grouped according to type), the acquisition records (grouped according to type). Finally, the author also inquired about the profile of the library personnel - their age, gender, position, educational attainment, computer-based skills and computer-related seminars that they have attended.